Exploring the relationship between corporate governance and firm value: evidence from LQ45 companies (2010-2014) - David, David; Lestari, Setyani Dwi; Saputro, Adi (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Companies listed in the LQ45 Index in Indonesia are considered to have good and stable performance. However, the influence of the proportion of independent commissioners, the size of the audit committee, leverage, and profitability on firm value still requires empirical research to provide a clearer picture. This study aims to examine the impact of these variables on firm value for companies listed in the LQ45 Index during the period 2010-2014. A quantitative method with panel data regression was used, and the sample was selected using purposive sampling based on the criteria of companies consistently listed in the LQ45 Index for five consecutive years. The independent variables studied include the proportion of independent commissioners, the size of the audit committee, leverage, and profitability, while firm value is the dependent variable. The results show that, on a partial basis, these variables do not have a significant effect on firm value, with probability values above 0.05. However, simultaneously, the four variables have a significant impact on firm value, with probability values below 0.05, indicating that these factors work together in influencing firm value. These findings indicate the importance of focusing on corporate governance and financial structure as a whole, even though these variables do not have a direct partial impact. This study provides insights for investors to consider external factors and economic policies that may have a greater effect on firm value.